Protection effectiveness of sacrificial cladding for near-field blast mitigation. (December 2022) - Zhou, Hongyuan; Zhang, Xuejian; Wang, Xiaojuan; Du, Xiuli; Yu, Shangjiang; Wang, Yonghui; Jiang, Jin
Highlights: Small face plate mass led to a significant increase in energy input to system. Foam core absorbed the majority of energy input to the system through crushing. Protection effectiveness was governed by energy input increase and energy absorption. Increasing face plate mass and foam core strength contributed to positive protection. Abstract: The protection effectiveness of the sacrificial cladding, consisting of a steel face plate and an aluminum foam core, subjected to near-field blast was experimentally and numerically investigated in the present study. It was proposed to evaluate the protection effect of the sacrificial cladding from two perspectives, namely, the increased energy input to the cladding-structure system as well as the increased energy absorption of the system. First, a blast test was conducted on the monolithic steel plates without and with sacrificial cladding under the TNT equivalent charge weights of 400 g and 1400 g, in which both the positive protection effect with 400 g charge weight as well as the negative protection effect with 1400 g charge weight were observed. Subsequently, numerical simulation with the model validated by the test data was employed to further investigate the blast mitigation effectiveness. The numerical results suggested that applying sacrificial cladding would lead to a significant increase in the energy input to the cladding-structure system, thus the negative protection effect of the cladding occurred when the increased energy input to the system was more than the energy absorption of the cladding. Furthermore, from the viewpoint of the energy input to the system and the energy absorption of the cladding, the influence of some important factors including the face plate thickness (mass), core strength, and stand-off distance on the protection effectiveness of the sacrificial cladding was further investigated with numerical simulation. The results showed that with cladding, a near-field blast with a small stand-off distance with the same charge weight was likely to lead to a negative protection effect due to the significantly increased energy input to the system. To realize the positive protection effect of the cladding, the measures of increasing the face plate thickness (mass) and the core strength were feasible since they could significantly reduce the energy input to the system and increase the energy absorption of the cladding simultaneously. The results in the present study provided a reference for the preliminary design and application of sacrificial cladding in structural protection.